Malaysia Islamic Bankers Perceptions of al-Qard al-Hasan - Noraini Mohd. Ariffin, Muhammad Akhyar Adnan (Review of Islamic Economics, 2011)
this paper studies te perceptions islamic bankers in Malaysia about the concept and operation of al-qard and al-hasan